The influence of non-performing loans (NPL), loan to deposit ratio (LDR), return on assets (ROA), and capital adequacy ratio (CAR) on credit growth in commercial banks in Indonesia - Novia Andini; Helma Malini; Giriati Giriati (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to examine the influence of Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Return on Assets (ROA), and Capital Adequacy Ratio (CAR) on credit growth in Conventional Commercial Banks in Indonesia during the 2020–2024 period. The background of this study is based on the inconsistency of previous research findings regarding internal banking factors that influence credit growth, as well as the limited empirical studies that specifically examine the post-COVID-19 pandemic period. This study uses a panel data regression method with a Fixed Effect Model (FEM) approach and involves conventional commercial banks as research objects for a five-year observation period. The results show that partially Non-Performing Loans (NPL) have a negative and significant effect on credit growth, while the Loan to Deposit Ratio (LDR) and Return on Assets (ROA) have a positive and significant effect on credit growth. Meanwhile, the Capital Adequacy Ratio (CAR) does not show a significant effect on credit growth. Simultaneously, these four variables are proven to have a significant effect on credit growth. This finding indicates that banking credit growth is more influenced by the level of credit risk, liquidity, and profitability than by capital adequacy factors.